Phytochemical study on the flower of Alstonia macrophylla Wall. ex G.Don (Apocynaceae) from Sumbawa Island, Indonesia - Putri Sri Andila; Tri Warseno; I Putu Agus Hendra Wibawa; I Gede Tirta (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2019)
Alstonia macrophylla Wall. ex G.Don is a native plant to South East Asia, belonging to Alstonia genus. This species has been reported to have numerous natural chemical compound which perfom multiple pharmacological and biological activities. The aim of this study was to investigated the phytochemical properties of the acetone extract of the flower of lstonia macrophylla Wall. ex G.Don. This is very interesting because phytochemical properties of its flower had been never reported yet. Alstonia macrophylla was harvested from the Natural Forest of Punik, Batu Dulang Village, Batulanteh Subdistrict, Sumbawa Regency, West Nusa Tenggara, Indonesia on Mei 2015. Acetone flower extract of A. macrophylla was analyzed with a GC-MS method to determine the chemical components. Result of GC–MS chromatogram revealed that there were 30 identified components in this extract. The major compounds were Cycloartenol acetate (17.11 %); 5H-1-Pyrindine (12.44 %); Lupeyl acetate (10.12%); Oleic acid (6.08 %); Benzenesulfonic acid, 4-hydroxy- (4.25 %); p-n-Amylphenol (4.23 %); and 4-Methylindole (4.22 %). Here, We reported the first study of phytochemical properties of A. macrophylla. This study help to understand further detail the potential of bioactive compound of A. macrophylla.